MICRO AND SMALL BUSINESS DEVELOPMENT AND INTERMEDIATE IN THE COOPERATIVE SERVICE AND MICRO, SMALL AND MEDIUM ENTERPRISES IN TONRA DISTRICT BONE REGENCY - Aslinda, Andi; Aztira, Mochammad Ardian; Guntur, Muhammad; Fitri, Anisa (Jurnal Aktor, 2024)
This research aims to find out the development of micro, small and medium enterprises in the Cooperatives and MSMEs Office in Tonra District. The research method is qualitative using a qualitative descriptive approach. The main instrument is the researcher himself with data collection techniques through observation, interview, and documentation techniques. The data analysis used in the study uses a qualitative interactive model with four flows, namely data reduction, data presentation and conclusion. The results of the study show that the development of Micro, Small, and Medium Enterprises at the Cooperatives and Micro, Small and Medium Enterprises (MSMEs) Office in Tonra District is considered to be quite well developed, where the findings of this research are supported from every dimension of SME development starting from the dimension of innovation promotion which the implementation of development by the Bone Regency SME Cooperative Office is carried out consistently by providing support to business actors to always innovate products and systems marketer.